Fundus imaging in patients with cataract: role for a variable wavelength scanning laser ophthalmoscope. Issue 10 (October 1995) - Kirkpatrick, J N; Manivannan, A; Gupta, A K; Hipwell, J; Forrester, J V; Sharp, P F
Abstract : AIMS--An investigation was carried out to compare the image quality of the ocular fundus obtained clinically, photographically, and with the scanning laser ophthalmoscope (SLO) at visible and infrared wavelengths in patients with significant cataract. METHODS--Nineteen patients admitted for routine cataract extraction were examined clinically by two independent observers to ascertain cataract type and clarity of fundus view with an indirect ophthalmoscope. Fundus photography and both confocal and direct (non-confocal) SLO imaging at 590 nm, 670 nm, and 830 nm were carried out after pupillary dilatation. Images obtained were graded independently using a recognised grading system. RESULTS--Quality of SLO images appeared to be superior to indirect ophthalmoscopy (p < 0.01) and fundus photography (p < 0.001) when graded subjectively. Quantitative analysis of contrast of retinal vessels demonstrated significantly higher contrast for the SLO compared with digitised fundus photographs at all wavelengths tested (p < 0.001), with highest contrast at 590 nm. Use of a confocal aperture significantly improved vessel contrast but may reduce overall image intensity. CONCLUSIONS--Scanning laser ophthalmoscopy may offer a method to observe and record fine fundus detail in patients who have marked cataract.